La música como elemento integrador en la formación de valores en el sub-nivel preparatoria. - Limaico, Mishel C. (2022)
The purpose of this research is to determine the incidence of music as an integrating element in the formation of values in children of the preparatory sublevel of the School of Basic Education “Children's Academy” of the Ibarra city. To deepen this study, objectives were proposed: 1) Theoretically, this study is based through bibliographic research on musical pedagogical currents that emphasize education in values. 2) Identify and implement technical-musical strategies such as songs for children and sound stories, aimed at reflection and internalization of messages implicit in them. 3) To obtain and analyze the results, the inductive method, qualitative approach, exploratory type and data collection techniques and instruments were used, as we worked with online surveys and questionnaires designed with pictograms according to the age of the children, to facilitate understanding of the topics covered. From the analysis and results obtained in the surveys applied to teachers, authorities and parents, and questionnaires to children, the most important finding was to verify that music influences not only the axiological aspect, but also contributes to the integral formation of students themselves; and 4) Make the pertinent recommendations for teachers to use musical strategies to promote changes in attitude, facilitate meaningful learning, enhance the intellectual and affective capacities of children, for a harmonious coexistence within the group.